Establishment of native grasses and their impact on exotic annuals in degraded box gum woodlands. (28th February 2017) - Cole, Ian; Prober, Suzanne; Lunt, Ian; Koen, Terry
Abstract: Restoration goals often involve the addition of new species to resident, degraded communities but in box gum woodlands such restoration is often constrained by competition from persistent exotic annuals that control critical ecological processes. Nutrient reduction (via carbon addition) and seed bank depletion are two approaches to reduce competition from exotic annuals but to be effective these treatments must allow establishment of species such as native grasses. This experiment was conducted in two degraded Austrostipa understoreys in the box gum woodlands of south‐east Australia. It compares the effects of carbon addition (sugar), seed depletion (spring burning or spring grazing) and combinations of carbon addition and seed depletion treatments on the establishment of C3 and C4 native grasses, and measured the effects of their establishment on soil nitrate concentration and exotic annuals. Treatments that reduced exotic annual abundance did not increase initial germination of the C4 native grasses, Bothriochloa or Themeda . However, sugar increased seedling survival of Themeda and Bothriochloa and grazing increased seedling survival of Bothriochloa, presumably by reducing effects of exotic annuals. Poa and Rytidosperma (C3 native grasses) failed to establish. Although we were unable to detect any reduction in soil nitrate concentration, swards with successful recruitment of C4 grasses suppressed exotic annuals more than the Austrostipa‐ only swards at one site (the other was affected by wildfire). Further, Austrostipa ‐ Themeda swards were more effective than Austrostipa‐Bothriochloa for suppressing exotics, pointing to a role for both functional and species identity in the degree of resistance conferred.